1986
DOI: 10.1017/s0272263100006082
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of the Recall Task to Measure L2 Reading Comprehension

Abstract: The free written recall task is used in much current L2 reading research (Bernhardt, 1983; Carrell, 1983, 1984a, 1984b; Connor, 1984; Lee & Ballman, in press). An examination of the work using this task as a measure of comprehension reveals variation in design and findings: measurement of quantity recalled, method of textual analysis, the language used to recall, the level of the learners, and pre-reading instructions given. The purpose of this paper is: (1) to elaborate the differences between studies usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 12 publications
5
60
0
1
Order By: Relevance
“…The current result also coincides with other research that has demonstrated issues with accurately assessing the WMC construct among populations with low verbal ability when tasks involve a significant language processing component (Nation et al, 1999). Finally, this result might also be related to findings that when bilinguals complete standardized tests in their non-native language, their performance tends to be lower, thus underestimating their true ability (Garcia, & Pearson, 1993;Lee, 1986;Mestre, 1986). Importantly, while linguistic information might prohibit the ability of RSpan to predict complex cognitive performance, this verbal information did not prohibit OSpan from still capturing the portion of RAPM variance commonly associated with WMC in native samples.…”
Section: Discussionsupporting
confidence: 90%
“…The current result also coincides with other research that has demonstrated issues with accurately assessing the WMC construct among populations with low verbal ability when tasks involve a significant language processing component (Nation et al, 1999). Finally, this result might also be related to findings that when bilinguals complete standardized tests in their non-native language, their performance tends to be lower, thus underestimating their true ability (Garcia, & Pearson, 1993;Lee, 1986;Mestre, 1986). Importantly, while linguistic information might prohibit the ability of RSpan to predict complex cognitive performance, this verbal information did not prohibit OSpan from still capturing the portion of RAPM variance commonly associated with WMC in native samples.…”
Section: Discussionsupporting
confidence: 90%
“…Lee (1986) has shown that second-language students present better recall of second-language text when allowed to produce the recall in their first language.-However, earlier studies on the process of bilingual development of minority children in the Netherlands have shown that by the end of the second grade Dutch tends to become the dominant language (Verhoeven, 1990(Verhoeven, ,1994.…”
Section: Discussionmentioning
confidence: 99%
“…For more than 2 decades, free-written-recall tests have served to measure the quantity of ideas recalled from L2 texts (Bernhardt, 1983;Brantmeier, 2002Brantmeier, , 2003Carrell, 1984a;Conner, 1984;Lee, 1986;Maxim, 2002;Young & Oxford, 1997). Written recall is an unstructured task that provides a comprehensive depiction of a reader's understanding because there is no tester interference and there are no retrieval cues to facilitate recall (Bernhardt, 1991).…”
Section: Prior Studies Of Test Typementioning
confidence: 99%